DELAYED FDG-PET/CT IMAGES IN PATIENTS WITH BRAIN TUMORS - IMPACT ON VISUAL AND SEMIQUANTITATIVE ASSESSMENT - Pavel H. Bochev; Aneliya Klisarova; Ara G. Kaprelyan; Borislav Chaushev; Zhivka Dancheva (Peytchinski Publishing, 2013)
Background: Despite the extensive use of FDG-PET/CT its role in brain tumor assessment remains controversial mostly because of the physiologically high brain uptake which easily obscures pathological processes. The wide availability of FDG, however, maintains the interest in FDG neuro-oncological applications. Objective: to evaluate the use of a late registration at 180min in patients with brain tumors, studied with FDG-PET/CT based on visual and semiquantitative analysis. Materials and methods: 38 patients with brain neoplasms and non-tumor structural lesions underwent a selective brain 18F-FDG PET/CT at two time points at 60 and 180 minutes after administration. Visual assessment was made by two readers with interobserver agreement calculation. Region ratio comparison with three different reference regions - the contralateral one, the white matter, and the cerebellum was used as a base for semiquantitative analysis. Results: Visual analysis showed better delineation of malignant lesion on late registrations with higher inter/intraobserver agreement as compared to the early images. Semiquantitative analysis demonstrated significant differences in early and late indices of metastases and gliomas, but failed in distinguishing gliomas from metastatic lesions and benign lesions.Conclusion: Delayed brain images with FDG-PET/CT at 180 min after injection provide better tumor delineation, higher accuracy, lower interobserver variations. The use of semiquantitative indices, irrespective of the reference region used, is of limited value